FACTORS ASSOCIATED WITH IRON ANEMIA DEFICIENCY IN CHILDREN AGED 12 TO 36 MONTHS IN PUBLIC HEALTH CENTER JATILAWANG, BANYUMAS CENTRAL JAVA - Sawitri Dewi; Purnomo Suryantoro; Sulistyaningsih Sulistyaningsih (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: According to the WHO, anemia prevalence in preschool children in the world obtained 47.4% from the total population of anemia sufferers. Indonesia collected 44.5%, therefore, it was included in the prone region to anemia cases in pre-school children. Iron Deficiency Anemia (IDA) was closely related to low birth weight babies and premature age, nutritional status, socio-economic and low maternal education. Children who experienced anemic iron deficiency (ADB) in infancy at risk of barriers to growth and development Method: This was a cross sectional study. The population covered all healthy children aged from 12 to 36 months. The sample on the study determined by consecutive sampling, 152 subjects were selected. Examination conducted by the method Hb and serum ferritin cyanmethemoglobin using ELISA method. Data analysis used chi-square and Logistic Regression. Results: The prevalence of IDA in Puskesmas Jatilawang Banyumas regency was 28 cases (18.4%). Malnutrition status, maternal education and family income contributed a significant relationship to the incidence of iron deficiency anemia in infants. Children with malnutrition status collected 10.5 higher risk than children with good nutrition. Children with mother education backgrounds were only at Elementary School or Junior High School supported 12 times greater iron deficiency anemia (95% CI: 12,16- 202.5), and children who came from families with incomes <Rp 1.100.000,- obtained 7.08 times iron deficiency anemia(95% CI: 1,70- 29.3). Conclusions: The prevalence of iron deficiency anemia was 18.4%. Malnutrition status, maternal education and family income were risk factors of anemic iron deficiency in children aged 12 to 36 months in Puskesmas Jatilawang Banyumas.